Inhibitors of Tax1‐PDZ Interactions Block HTLV‐1 Viral Transmission by Changing EV Composition - Jedidja Puttemans; Yasmine Brammerloo; Karim Blibek; Jeremy Blavier; Thandokuhle Ntombela; Inge Van Molle; Julie Joseph; Julien Olivet; Deeya Saha; Manon Degey; Malik Hamaidia; Pooja Jain; et al. (Journal of Extracellular Vesicles)
ABSTRACT Extracellular vesicles (EVs) are known to facilitate infection by enveloped RNA viruses including the Human T‐cell leukemia virus type‐1 (HTLV‐1). HTLV‐1‐encoded proteins, like the transactivator and oncoprotein Tax‐1, are loaded into EVs but their precise impact on EV cargos is not yet known. Here, we report a comprehensive interaction map between Tax‐1 and the human PDZ (PSD95/DLG/ZO‐1) proteins that regulate EVs formation and composition. We show that Tax‐1 interacts with more than one‐third of hPDZome components, including proteins involved in cell cycle, cell–cell junctions, cytoskeleton organization and membrane complex assembly. We extensively characterized Tax‐1 interaction with syntenin‐1, an evolutionary conserved PDZ hub that controls EV biogenesis. Using nuclear magnetic resonance (NMR) spectroscopy, we have determined the structural basis of the interaction between the C‐terminal PDZ binding motif of Tax‐1, and two PDZ domains of syntenin‐1. Importantly, we show that a small molecule able to inhibit HTLV‐1 cell‐to‐cell transmission breaks the Tax‐1/syntenin‐1 interaction, impacts the levels of syntenin‐1 and viral proteins in EVs, and shifts the EV composition toward cellular antiviral proteins and microRNAs, including the miR‐320 family. Consequently, we demonstrate that mimics of miR‐320c, encapsulated into EVs, have antiviral activities with a potential to be used against HTLV‐1 induced diseases.